Autoimmune pancreatitis - Dite, Petr; Nechutova, Hana; Uvirova, Magdalena; Dvorackova, Jana; Kianicka, Bohuslav; Martinek, Arnost (Biomedical papers, 2014)
Introduction: Autoimmune pancreatitis (AIP) is the specific type of chronic pancreatitis due to autoimmune background and mechanism.Characteristics. The main clinical symptoms of AIP are obstructive jaundice and abdominal discomfort. The typical histological findings are lymphocytes and IgG4 plasma cells infiltration, fibrosis and venulitis within pancreatic gland. Plasma level of IgG4 is usually extremely high.Objectives: Diagnosis: High level IgG4 positive plasma cells in serum, lymphoplasmatic infiltration found on histological staining of pancreatic tissue, ``sausage-like'' pancreas in ultrasound and CT scans, and response to steroid therapy are crucial for making of diagnosis.Classification of AIP: AIP can be classified into two subtypes. Type 1 was recognized as the pancreatic manifestation of multiorgan disorder, called IgG4 related disease. Type 2 is a pancreas-specific disorder not associated with IgG4, with similar histological signs as type 1, but also with the positivity of GEL (granulocythic epithelial lesion).Results: Therapy: Due to its high effectivity in AIP treatment, steroid therapy is the first-line option. The alternative therapy is using immunosuppressants (azathioprine). Recently, there are also first experience in biological therapy already published.Conslusion. Before the start of AIP therapy - the differential diagnosis between pancreatic cancer and AIP is essential.
Keywords: chronic pancreatitis; autoimmune pancreatitis; immunoglobulines; IgG4; steroids; extrapancreatic lesions; pancreatic biopsy